Comparative Analysis of Institutional Theories: Economic Traditions of Veblen, Commons and Mitchell - Mahmoud Mashhadi Ahmad (پژوهش‌های برنامه و توسعه)
Institutional economics is one of the most important economic traditions that not only challenged the mainstream economics but also opened up new horizons in the domain of economic knowledge by identifying the philosophical and theoretical outlets and gaps of orthodox economics through its path-breaking studies. Veblen, Commons and Mitchell are generally cited as the main founders of institutional economics. Those who in the early twentieth century established their institutional approach with their huge philosophical and theoretical efforts. Considering the importance of their scientific work in economics,, this article will attempt to reflect on some of their most important scientific achievements. Of course, this will be done on two levels. First, the ideas of these three economists will be discussed separately, and some of the most important components of their ideas will be analyzed. In the following, and because of the relative independence of these three prominent thinkers, we will compare their thoughts and ideas in order to identify some of their similarities and differences.